A Web-Based Cultural Competency Training for Medical Students: A Randomized Trial. (May 2015) - Carpenter, Riley; Estrada, Carlos A.; Medrano, Martha; Smith, Ann; Massie, F. Stanford
Abstract : Background: The objectives of this research were to compare a Web-based curriculum with a traditional lecture format on medical students' cultural competency attitudes using a standardized instrument and to examine the internal consistency of the standardized instrument. Methods: In 2010, we randomized all 180 1st-year medical students into a Web-based (intervention group) or a lecture-based (control group) cultural competency training. The main outcome was the overall score on the Health Belief Attitudes Survey (1 = lowest, 6 = highest). We examined internal consistency with factor analysis. Results: No differences were observed in the overall median scores between the intervention (median 5.2; 25th percentile [Q1] 4.9, 75th percentile [Q3] 5.5) and the control groups (median 5.3, Q1 4.9, Q3 5.6) ( P = 0.77). The internal consistency of the 2 main subcomponents was good (Cronbach's alpha = 0.83) to acceptable (Cronbach's alpha = 0.69). Conclusions: A Web-based and a lecture-based cultural competency training strategies were associated with equally high positive attitudes among 1st-year medical students. These findings warrant further evaluation of Web-based cultural competency educational interventions.